Ultrafast charge generation, high and balanced charge carrier mobilities in organo halide perovskite solar cell - Ponseca, Carlito S.; Abdellah, Mohamed; Zheng, Kaibo; Yartsev, Arkady ; 0000-0003-4941-4848; Pascher, Tobjörn; Harlang, Tobias; Chabera, Pavel; Pullerits, Tonu; Stepanov, Andrey; Wolf, Jean-Pierre; Sundström, Villy (19th International Conference on Ultrafast Phenomena, UP 2014, Okinawa, Japan, 2014-07-07 - 2014-07-11, 2014)
Using terahertz and transient absorption spectroscopy, carrier dynamics in organo halide perovskite solar cell is probed. Charge generation is <100 fs, followed by 2 ps charge formation with balanced electron hole mobility of 20 cm2V-1s-1.